2021
DOI: 10.1038/s41598-021-83782-0
|View full text |Cite
|
Sign up to set email alerts
|

A prospective 5-year study on the use of transient elastography to monitor the improvement of non-alcoholic fatty liver disease following bariatric surgery

Abstract: Liver stiffness measurement (LSM) by transient elastography (TE) is a non-invasive assessment for diagnosing and staging liver fibrosis in non-alcoholic fatty liver disease (NAFLD). Evidence on its role as a longitudinal monitoring tool is lacking. This study aims to evaluate the role of TE in monitoring NAFLD improvement following bariatric surgery. This study prospectively recruited 101 morbidly obese patients undergoing laparoscopic bariatric surgery for intraoperative liver biopsy. Thirty-seven patients of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(45 reference statements)
0
11
0
2
Order By: Relevance
“…With newer models, liver fibrosis can now be measured by liver stiffness measurement (LSM), and liver steatosis can be measured by controlled attenuation parameter (CAP) [ 66 ]. There are several benefits of TE, including its low cost, fast procedure time, immediate result availability, good reproducibility, and ability to be performed in an outpatient setting [ 67 ]. Several cross-sectional studies have investigated how it helps diagnose NAFLD and assess its severity [ 63 , 65 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…With newer models, liver fibrosis can now be measured by liver stiffness measurement (LSM), and liver steatosis can be measured by controlled attenuation parameter (CAP) [ 66 ]. There are several benefits of TE, including its low cost, fast procedure time, immediate result availability, good reproducibility, and ability to be performed in an outpatient setting [ 67 ]. Several cross-sectional studies have investigated how it helps diagnose NAFLD and assess its severity [ 63 , 65 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a long‐term follow‐up study of 102 obese Japanese patients undergoing bariatric surgery demonstrated that liver fat accumulation and visceral fat areas were significantly improved at 1 year after surgery, and the decrease in BMI, body fat percentage, and basal metabolic rate prolonged for at least 5 years 147 . In 37 Asian patients receiving annual TE following bariatric surgery, the mean LSM reduced significantly from baseline values of 9.8‐6.8 kPa at 5 years after operation 148 . The latest APASL guidelines recommend that bariatric surgery can be considered for NAFLD only if the following are met: (a) presence of other indications such as BMI > 30 kg/m 2 (for Asian people) and (b) absence of cirrhosis with high perioperative risk 27 …”
Section: Assessment and Management Of Nafldmentioning
confidence: 99%
“…38,39 Furthermore, in recent years, liver stiffness measurement (LSM) by transient elastography (TE) is considered as one of the most relevant lines of investigation with respect to the non-invasive screening of hepatic fibrosis. [40][41][42] As a result, several scoring systems based on the combination of TE with other clinical and/or laboratory parameters have been proposed to improve diagnostic accuracy for fibrosis staging.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 In this context, there is increasing evidence suggesting that NITs for fibrosis could be used as important predictors of long-term clinical outcomes. 39,41,42,46,47 The question as to whether laboratory-and/or imaging-based NIT scores reflecting severity of hepatic fibrosis could be associated with the burden of NAFLD from the patient's perspective is not fully investigated. By taking advantage of the Global NAFLD/ NASH Registry and focusing on the NIT and PRO data collected from patients with NAFLD in Turkey, this registry-based, cross-sectional study assessed the association of PROs with select NITs for fibrosis including FAST, Agile 3+ and Agile 4 scores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation